Chinook materials, C. F. Voegelin Papers - Voegelin, C. F. (Charles Frederick), 1906-1986
Three items relating to the Chinook (Chinookan) language have been identified in the C. F. Voegelin Papers. They are all in Subcollection II, and consist of a folder with information on "Miscellaneous languages"--including Inuit ("Eskimo"), Takelma, Siouan, Maidu, Chinook, Tsimshian, Haida, Coos, and Siuslawan (Lower Umpqua)--in Series II. Research Notes, Subseries I. Eskimo-Aleutian; a folder on "Chinookan: Chinook, Wishram, Kathlamet" in Series II. Research Notes, Subseries VI. Penutian, including Mayan and Zoque; and a Chinook folder in Series III. Works by Voegelin, Subseries I: General works.